2011
DOI: 10.1002/hed.21448
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of cervical lymphadenopathy: Role of high‐resolution and color Doppler imaging

Abstract: Sonographic findings have a high accuracy in differentiating benign from malignant cervical lymph nodes. An ultrasound scan can be used as the first-line imaging tool in the diagnostic evaluation of cervical lymphadenopathy, especially in developing countries like India due to its ease, noninvasiveness, reproducibility, and cost effectiveness. It can also be used as an imaging tool for the guided aspirations. However, because of some overlapping in sonographic appearances of benign and malignant nodes, this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
58
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 13 publications
8
58
0
3
Order By: Relevance
“…Ultrasonography is the first imaging technique in these cases due to a good accessibility of the cervical region, high spatial resolution, and a soft tissue discrimination [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonography is the first imaging technique in these cases due to a good accessibility of the cervical region, high spatial resolution, and a soft tissue discrimination [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The oval shape (shape index <0.5 or Solbiati index-ratio of the longitudinal to the short axis diameters-above than 2 or 1.5), the homogenous structure, the uniform cortical width, the hyperechoic hilum, the well defined margins, and the hilar vascular pattern are characteristics of inflammatory lymph nodes. Signs of malignant lymph nodes are considered to be the hypoechoic and heterogeneous texture, the round shape, the lack of hyperechoic hilum, the ill-defined margins, and the peripheral or mixed pattern of vascularization [4,5]. Until now no absolute criterion has been defined due to the false positive and false negative aspects encountered in normal and pathological lymph nodes [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies in which cervical lymph nodes were evaluated, it was indicated that peripheral blood supply shows malignant character better and central blood supply shows benign character better with a large hypoechoic round appearance (21,22). As scanning by echo-enhancement was not used in this study, the blood flow pattern in lymph nodes was not evaluated.…”
Section: Discussionmentioning
confidence: 96%
“…5 Ultrasound may also be used as part of the investigation; this has shown sensitivity in the differentiation of benign and malignant cervical lymphadenopathy, 6 especially when used in combination with FNAC. 7 Lymph node biopsy is currently recommended for a definitive diagnosis of lymphoma. 3 Therefore, the provision of an efficient service depends largely on the referring clinician's ability to establish the most appropriate diagnostic pathway based on the patient's history and examination findings.…”
Section: Discussionmentioning
confidence: 99%